ANALYSIS OF FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF PARIGI MOUTONG DISTRICT - Wahyu, Wahyu; Afriza, Afriza; Muslimin, Muslimin; Husnah, Husnah (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to analyze the financial performance of the local government of Parigi Moutong District in the period 2016-2021 by using the ratio analysis method of PAD growth, decentralization, independence, PAD effectiveness, expenditure growth, expenditure compatibility consisting of operational and capital expenditures, and expenditure efficiency by using a quantitative descriptive approach. The results of the research show that (1) The PAD growth analysis has a positive category with an average percentage value of 11.73%, and (2) The ratio analysis of the degree of decentralization has a very low category with a percentage value of 9.07%, (3) Ratio analysis of regional financial independence has an instructive category with a percentage value of 13.14%, (4) PAD effectiveness ratio analysis has a very effective category with a percentage value of 105.40%, (5) Growth Analysis expenditure has a positive category with a percentage value of 4.76%, (6) The analysis of the compatibility ratio consisting of operational and capital expenditure has a balanced category with a percentage value of 64.13% and 16.20%. (7) The expenditure efficiency ratio analysis has an efficient category with a percentage value of 94.53. Keywords: PAD Growth, Degree of Decentralization, Independence, PAD Effectiveness, Expenditure Growth, Harmony, Expenditure Efficiency.